Relationship Between the Creative Leadership of Administrators and Being an Innovative Schools Under the Office of Kamphaeng Phet Primary Educational Service Area 1 - Nenaiam, Angkanthip; Sawangmek, Taweesak (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to 1) Study the creative leadership of school administrators, 2) Study the status of being innovative schools, and 3) Study the relationship between the creative leadership of school administrators and the status of being innovative schools under the Office of Kamphaeng Phet Primary Educational Service Area 1. The sample consisted of school administrators and teachers under the jurisdiction of the Office of Kamphaeng Phet Primary Educational Service Area 1 during the 2024 academic year, totaling 322 participants. The research instrument was a five-point Likert scale questionnaire. Data were analyzed using mean, standard deviation, and Pearson’s correlation coefficient. The research findings revealed that 1) The creative leadership of school administrators under the Kamphaeng Phet Primary Education Service Area Office 1, both overall and in each aspect, was at a high level. 2) The schools under the Kamphaeng Phet Primary Education Service Area Office 1 were considered innovative schools, with overall and individual aspects also at a high level. 3) The relationship between the creative leadership of school administrators and the status of being an innovative school under the Kamphaeng Phet Primary Education Service Area Office 1 was positively high and statistically significant at the .01 level.